A single component photoimaging system with styrene copolymers having t-BOC-protected quinizarin dye precursors and photoacid generating groups in a single polymer chain - Yoo, JH; Kim, SY; Cho, I; Kim, JM; Ahn, KD; Lee, JH (ELSEVIER SCI LTD, 2004)
A styrene monomer tBQSt, having a tert-butyloxycarbonyloxy (t-BOC)-protected quinizarin dye precursor as a pendent, has been copolymerized with N-(tosyloxy)maleimide (TsOMI) to obtain a dual functional polymer P(tBQSt/TsOMI). The polymer P(tBQSt/TsOMI), as a single component photoimaging system without using an external photoacid generator (PAG), was applied for fluorescent photopatterning by dry process based on the chemical amplification (CA) process. The TsOMI units in the polymer chains were responsible for photochemical generation of p-toluenesulfonic acid by UV exposure and the acid generated in the solution cast polymer film induced the catalytic deprotection of acid labile t-BOC groups of the quinizarin dye precursors. Accordingly, the quinizarin moieties were regenerated in the polymer chains by the CA process, thereby recovering the original color and fluorescence of the quinizarin dye. Fluorescent patterns were readily delineated on the thin polymer films by imagewise UV exposure even without a wet development process. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: CHEMICAL AMPLIFICATION RESISTS